Mirror, mirror - Calonita, Jen (Twisted tale., 2019)
Presents a retelling of the classic fairy tale "Snow White" with a plot twist. When Snow White's evil step-mother takes over the kingdom, she sets out to stop her with the help of her dwarf friends and a kind prince she's come to care for very much. But the Evil Queen won't let go of her power that easily and she sets her sights on hurting those Snow White loves.